The Abu Ghraib torture photographs: news frames, visual culture and the power of images - Andén-Papadopoulos, Kari (Henry Stewart Talks, 2010)
Problems of how iconic images in the news exercise power in the shaping of news, politics and public opinion, Visual culture studies perspective on how media images and their viewers make meaning, Specific analysis of the meaning and impact of the Abu Ghraib prison photographs, Critical assessment of the role and limitations of so called 'dominant' news frames in shaping the wider cultural perception of iconic news photographs